2021
DOI: 10.3390/genes12111779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of G-Quadruplexes and Chronic Inflammation on Genome Instability: Additive Effects during Carcinogenesis

Abstract: Genome instability is an enabling characteristic of cancer, essential for cancer cell evolution. Hotspots of genome instability, from small-scale point mutations to large-scale structural variants, are associated with sequences that potentially form non-B DNA structures. G-quadruplex (G4) forming motifs are enriched at structural variant endpoints in cancer genomes. Chronic inflammation is a physiological state underlying cancer development, and oxidative DNA damage is commonly invoked to explain how inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…Compared with the non-G quadruplex ODN, G quadruplex ODN blocked more efficiently TLR7- and TLR9-mediated innate immune responses ( Römmler et al, 2013 ). This phenomenon might be related with the regulatory role of G quadruplex in inflammatory-related gene promoters ( Stein and Eckert, 2021 ). However, more is not always better; some new evidence suggested that inhibitory ODNs containing many G triplets, or quadruples were easy to form higher order structures, also called G4 stacks, which made their immunological and pharmacological behaviors unpredictable ( Lenert, 2010 ; Römmler et al, 2013 ; Zuffo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the non-G quadruplex ODN, G quadruplex ODN blocked more efficiently TLR7- and TLR9-mediated innate immune responses ( Römmler et al, 2013 ). This phenomenon might be related with the regulatory role of G quadruplex in inflammatory-related gene promoters ( Stein and Eckert, 2021 ). However, more is not always better; some new evidence suggested that inhibitory ODNs containing many G triplets, or quadruples were easy to form higher order structures, also called G4 stacks, which made their immunological and pharmacological behaviors unpredictable ( Lenert, 2010 ; Römmler et al, 2013 ; Zuffo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides direct induction of mutations as a result of oxidative DNA damage, oxidative stress can contribute to genome instability and epigenetic dysregulation. Repetitive sequences, which are particularly susceptible to DNA oxidation, can form secondary DNA structures upon oxidation . During DNA replication, recruitment of a special but error-prone DNA polymerase to these secondary DNA structures is needed for continuation of synthesis, ultimately contributing to genome instability .…”
Section: Oxidative Stress In Relation To the Cancer Hallmarksmentioning
confidence: 99%
“…Repetitive sequences, which are particularly susceptible to DNA oxidation, can form secondary DNA structures upon oxidation . During DNA replication, recruitment of a special but error-prone DNA polymerase to these secondary DNA structures is needed for continuation of synthesis, ultimately contributing to genome instability . Furthermore, ROS-induced expression of Bcl-2, following NRF2, , NF-κB, or STAT3/5 signaling, can inhibit DNA double-strand break (DSB) repair .…”
Section: Oxidative Stress In Relation To the Cancer Hallmarksmentioning
confidence: 99%
“…Systemic inflammatory responses can aggravate malnutrition in patients. Inflammatory indicators have certain reference values in the diagnosis and prognosis of various malignant tumors, and research has confirmed that inflammation may promote tumor progression ( 97 ). Zhang et al ( 98 ) found that the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were valuable for predicting LNM in gastric cancer.…”
Section: Role Of the Tumor Microenvironment In The Lymphatic Metastas...mentioning
confidence: 99%